Inertial Dynamometer for Shell Eco-marathon Engine: Validation - Filipe da Silva Cardoso, Daniel; Manuel Figueira Neves Amaro, João; Manuel Oliveira Fael, Paulo (KnE Engineering, 2020)
This paper aims to validate the construction of an inertia dynamometer. These types of dynamometers allow easy characterization of internal combustion engines. To validate the dynamometer, tests were carried out with the same engine (Honda GX 160) installed in the UBIAN car and kart, which after calculating the inertia and measuring engine acceleration in each test performed, allows to create the torque characteristic curve from the engine. Keywords: Inertia, Dynamometer, Torque, Flywheel, UBIAN